1992
DOI: 10.1111/j.1479-828x.1992.tb02841.x
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Delivery in Diabetic Pregnancy: A 10‐Year Review

Abstract: The approach of term in the pregnancy of a diabetic woman is a time of anxiety for patient and physician alike. The impact of a conservative approach to the timing of delivery is outlined in this review of the clinical course and outcome of 276 pregnancies of diabetic women, delivered at the National Maternity Hospital, Dublin between 1981 and 1990. The mean gestation at delivery was 39 weeks, 229 patients (83%) delivered at or beyond 38 weeks and 112 patients (41%) delivered at or beyond 40 weeks. The overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The establishment of prepregnancy counselling, and combined specialist diabetic antenatal clinics has had a positive impact on the management of pregnancies complicated by diabetes. It has also been reported that the severity of antenatal fetal complications decreases as glycaemic control is improved [11,35,36]. The small size of the current study limits any firm conclusions, but supports previously published work.…”
Section: Discussionsupporting
confidence: 67%
“…The establishment of prepregnancy counselling, and combined specialist diabetic antenatal clinics has had a positive impact on the management of pregnancies complicated by diabetes. It has also been reported that the severity of antenatal fetal complications decreases as glycaemic control is improved [11,35,36]. The small size of the current study limits any firm conclusions, but supports previously published work.…”
Section: Discussionsupporting
confidence: 67%
“…The GDM management guidelines from the Australasian Diabetes In Pregnancy Society (ADIPS), which is endorsed by the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG), state that "childbirth before full term is not indicated unless there is evidence of macrosomia, polyhydramnios, poor metabolic control or other obstetric indications" (Rasmussen et al, 1992;Hoffman et al, 1998). Thus, induction of labour may be considered 'elective' (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A very big baby may reflect diabetic fetopathy and fetal hyperinsulinaemia, and hence may indicate a baby at risk in utero of hypoxia and acidosis 1,2 . All six late pregnancy stillbirths reported in one study were macrosomic with polyhydramnios 3 . A review of national data from Sweden found four ‘unexplained’ intrauterine deaths at > 34 weeks.…”
Section: Introductionmentioning
confidence: 92%